Nigeria healthcare worker SARS-CoV-2 serology study: Results from a prospective, longitudinal cohort. - Dike B Ojji; Amelia Sancilio; Gabriel L Shedul; Ikechukwu A Orji; Aashima Chopra; Joel Abu; Blessing Akor; Nana Ripiye; Funmi Akinlade; Douglas Okoye; Emmanuel Okpetu; Helen Eze; et al. (Public Library of Science (PLoS), 2023)
Healthcare workers, both globally and in Nigeria, have an increased risk for SARS-CoV-2 infection compared with the general population due to higher risk contacts, including occupational exposures. In addition, primary healthcare workers represent an important group for estimating prior infection to SARS-CoV-2 because they work at the first point-of-contact for most patients yet have not been included in prior COVID-19 seroepidemiology research in Nigeria. We sought to evaluate baseline seroprevalence, rates of seroconversion (IgG- to IgG+) and seroreversion (IgG+ to IgG-), change in IgG concentration at 3- and 6-month follow-up, and factors associated with seropositivity. From June 2020 to December 2020, we conducted a longitudinal seroepidemiology study among frontline health care workers in Nigeria using a validated dried blood spot assay. Among 525 participants, mean (SD) age was 39.1 (9.7) years, 61.0% were female, and 45.1% were community health workers. The six-month follow-up rate was 93.5%. Seropositivity rates increased from 31% (95% CI: 27%, 35%) at baseline to 45% (95% CI: 40%, 49%) at 3-month follow-up, and 70% (95% CI: 66%, 74%) at 6-month follow-up. There was a corresponding increase in IgG levels from baseline (median = 0.18 ug/mL) to 3-month (median = 0.35 ug/mL) and 6-month follow-up (median = 0.59 ug/mL, Ptrend < .0001). A minority of participants reported symptoms from February 2020 until baseline (12.2%) or during 3-month (6.6%) or 6-month (7.5%) follow-up. only 1 participant was hospitalized. This study demonstrated high baseline, 3-month and 6-month follow-up prevalence of IgG antibodies to SARS-CoV-2 during the first two waves of the COVID-19 pandemic in Nigeria among a cohort of unvaccinated frontline healthcare workers, including primary healthcare workers despite low symptomatology. These results may have implications in state- and national-level disease pandemic modeling. Trial registration: NCT04158154.